Program for Climate Smart Livestock Systems (PCSL): Futures workshop, Uganda, March 2021 - Kitololo, L.; Pereira, L.; Cramer, Laura K.; Mugumya, R.; Vrettos, C.; Zaake, Paul; Ericksen, Polly J. (International Livestock Research Institute, 2021)
The International Livestock Research Institute (ILRI) is implementing the Program for Climate Smart Livestock (PCSL) in Kenya, Uganda, and Ethiopia. PCSL is designed to build the capacity of governments, the private sector, and livestock keepers towards improving livestock productivity, reducing greenhouse gas emissions while adapting to climate change. In March 2021, ILRI held a workshop with relevant stakeholders to discuss potential transformative pathways for the livestock sector in Uganda.